The Pemilihan Runway Berdasarkan Arah Angin Tiap Musim Di Bandar Udara Budiarto - Arum Hidayati; Ratna Komala; Henry Riyandi; Herman Susanto (Politeknik Penerbangan Indonesia Curug, 2023)
Take off and landing process must consider the direction and speed of the wind in order to avoid fatal incidents on aircraft, especially for small-bodied aircraft such as those owned by the Indonesian Aviation Polytechnic Curug (PPIC). Fast, precise and accurate wind information can be a decision support for pilots and ATC to determine a safe runway for takeoff and takeoff processes. Changes in regional scale wind direction occur monsoonally in most areas in Indonesia which affect the change in surface wind direction. This study aims to find the direction of most winds blowing at Budiarto Airport using the WindRose (Mawar Angin) application. By knowing the dominant wind direction based on the month and season to determine the runway to be used at Budiarto Airport. Hourly wind direction and speed data from the Budiarto Meteorological Station for a five-year period from January 2015 to December 2019. From the results of the study, it was concluded that based on the value of headwind and crosswind events during 2015-2019 the use of Runway 04 was good to use during the rainy season and Runway 12 during the dry season, while in the transition season the Runway is best used is Runway 04. The decision to use the runway is still left to the relevant parties such as ATC and the Pilot by considering other things other than information on wind direction and speed